Exploring ESL students’ perceptions of their digital reading skills - John, Gilbert (2014)
This study investigates English language learners’ interaction with paper text and web text reading. Four main research questions shape the study: 1) What evidence exists to suggest that ESL learners use different strategies when reading printed text as opposed to reading web text? 2) What metacognitive strategies do ESL students use and report when reading and learning from printed and web-based texts? 3) What issues do ESL learners identify in relation to their use of the Internet? and 4) What are the implications for ESL pedagogy? While research has increasingly been focused on second language reading, it has primarily been centered on how the learner interacts and decodes printed text. However, little research has been conducted on how the English language learner processes web text, navigates the Internet, or evaluates and comprehends what he/she is reading through the use of digital literacy skills and metacognitive strategies.